Predicting intentions towards long-term antidepressant use in the management of people with depression in primary care: A longitudinal survey study - Rachel Dewar-Haggart; Ingrid Muller; Felicity Bishop; Adam W. A. Geraghty; Beth Stuart; Tony Kendrick (PLoS ONE, 2025)
Background Over the last two decades, antidepressant prescribing in the UK has increased considerably, due to an increased number of people staying on antidepressants for longer. Even when treatment is no longer clinically indicated, qualitative research suggests many people continue due to a fear of depressive relapse or antidepressant withdrawal symptoms. The quantitative effects of peoples’ beliefs and attitudes towards long-term antidepressant use remain relatively unexplored. Objectives To determine the extent to which beliefs and attitudes towards antidepressant treatment are associated with intentions to stop or continue long-term use; and whether intentions translate into actual discontinuation. Methods A questionnaire survey formed the main component of an embedded mixed-methods study. Twenty general practices posted questionnaires to adults aged over 18 receiving continuous antidepressant prescriptions for over two years. Outcomes and explanatory variables were determined using an extended model of the Theory of Planned Behaviour, conducting exploratory descriptive and regression analyses. The primary outcome was participants’ intentions to discontinue antidepressants. The secondary outcome of behaviour change was determined by any change in antidepressant dosage at six months. Results 277 people were surveyed from 20 practices, with 10 years median antidepressant duration. Mean questionnaire scores for intention and subjective norms towards starting to come off antidepressants were low, and 85% of participants declared that continuing their antidepressant was necessary. Prescribing outcomes retrieved from 175 participants’ medical records six months after they completed the survey found 86% had not changed their antidepressant, 9% reduced the dose, only 1% discontinued their antidepressant, and 4% increased the dose. All Theory of Planned Behaviour constructs and concerns were associated with intentions, with more favourable attitudes towards stopping and subjective norms having the strongest associations towards intentions to discontinue antidepressant use. Conclusion Given few intentions to stop taking antidepressants, patients should be made more aware of the importance of ongoing antidepressant monitoring and review from their primary care practitioners. This would promote discussion to support an attitudinal change and initiation of antidepressant tapering where appropriate.